La valutazione economica del trattamento farmacologico con antipsicotici nella schizofrenia: una revisione sistematica della letteratura - Ravasio, R. (Farmeconomia. Health Economics and Therapeutic Pathways, 2005)
Schizophrenia is a chronic, severe, and disabling brain disease. Approximately 1 percent of the population develops schizophrenia during their lifetime. Available treatments can relieve many symptoms, but most people with schizophrenia continue to suffer some symptoms throughout their lives; it has been estimated that no more than one in five individuals recovers completely. The introduction of second-generation antipsychotics, also defined as atypicals, has increased the therapeutic options available for individuals with schizophrenia. Potential benefits of these agents include a more favourable profile in terms of positive and negative symptoms, less adverse effects and better cognitive functioning than first-generation antipsychotics. It is uncertain whether atypical antipsychotic agents, as prescribed in ordinary practice, are a cost-effective alternative to conventional agents. This study examined the financial and clinical implications of using atypical antipsychotics in the treatment of schizophrenia, considering both related costs and consequences. To elaborate the paper, we reviewed 8 economical studies regarding the comparison between atypical and typical antipsychotics, published in the years 1998-2004. In 5 studies atypical antipsychotics were cost-saving compared to typical, in 2 studies they were cost-neutral and in one study they resulted cost-effective. Consequently typical antipsychotics were cost-saving just in one study.